PENGARUH TRANSPARANSI DAN AKUNTABILITAS TERHADAP PENGELOLAAN PENDAPATAN ASLI DAERAH DI KOTA LHOKSEUMAWE - Cut Humaira; Edi Zulfiar; Maryana Maryana (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2019)
This research is about the effect of transparency and accountability on the management of local revenue at the Regional Financial and Asset Management Agency (BPKAD) of Lhokseumawe City. The purpose of this study is to examine the effect of transparency and accountability on the management of local revenue at the Regional Financial and Asset Agency (BPKAD) Lhokseumawe City. The data used in this study is a questionnaire to 29 employees who are used as research samples. Data processing was carried out with the help of multiple linear regression models with the SPSS version 17 program. The results showed that transparency and accountability had an effect on the management of local revenue at the Regional Finance and Asset Agency (BPKAD) Lhokseumawe City.